TRADITIONAL CONFLICT AND ITS INTERVENTIONS - Muhlis, Muhlis (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2013)
The Ngali-Renda conflict is habituated. It has taken for years. It has grown in its severity. It is not the case that the people of Ngali and Renda and the government do nothing in dealing with the conflict. However, the conflict is still there and waiting its trigger to appear. This research is significant in that it analyzes the traditional factors and interventions of the conflict. Applying qualitative research and historical, socio-cultural and phenomenological approaches showed that the Ngali-Renda conflict transformed from ndempa (empty-handed fighting) to lewa (armed fighting). Ndempa implied the spirit of honesty, openness and patriotism. It occurred every year in rest period of cultivation and took one or two month. Although ndempa was kapoda ade (serious and violent), it was kadihi ade (no intention to do harm) and for play and pleasure. On the contrary, lewa was more violent and caused casualties because the fighters used big knifes, arrows and firearms.***Konflik Ngali-Renda merupakan konflik yang sudah biasa terjadi. Konflik ini merupakan konflik kekerasan. Masyarakat Ngali-renda maupun pemerintah telah berupaya untuk mengatasi konflik tersebut, namun belum menampakkan hasil. Penelitian ini memiliki ati penting untuk melihat faktor-faktor tradisional dan penanganan konflik yang telah dilakukan. Tampak dalam penelitian ini bahwa konflik Ngali-Renda merupakan transformasi konflik dari ndempa (perkelahian tanpa senjata) menjadi lewa (perkelahian dengan senjata). Ndempa memiliki makna semangat kejujuran, keterbukaan, dan patriotisme. Tradisi ini merupakan tradisi tahunan, yang dilakukan setelah musim tanam dan berlangsung selama satu hingga dua bulan. Walaupun ndempa disebut kapoda ade (sungguh-sungguh dan keras) namun kadihe ade (tidak berniat untuk menyakiti), dan hanya untuk tujuan permainan dan kesenangan. Sementara lewa lebih keras dan menyebabkan korban luka karena pelaku menggunakan pedang, panah, serta senjata api.